Pengaruh Penerapan Sistem Akuntansi Keuangan Daerah, Kejelasan Sasaran Anggaran Dan Akuntabilitas Keuangan Terhadap Akuntabilitas Kinerja Instansi Pemerintah Studi Pada Pemerintah Provinsi Daerah Istimewa Yogyakarta - Putri Ardiyan, Novita; Binawati, Enita (Jurnal Solusi, 2019)
This study aimed to examine the influence of the implementation of regional financial accounting system, budget goal clarity, and financial accountability towards the accountability performance of government agencies. The object of this research was the regional working units (SKPD) in Yogyakarta special region (DIY). The sampling technique in this research was purposive sampling technique; it is a sampling technique with a certain considerations. The sample of this research was employees in the financial sector in each regional working unit (SKPD). The data in this study are primary data. The data were collected using questionnaires distributed directly to the respondents. The analytical method, which was used in this research, was Multiple Linear Regression model. The results of this research and the hypothesis testing showed that the application of a variable area of regional financial accounting system and budget goal clarity had a significant influence on the performance accountability of government agencies. On the other hand, the financial accountability did not have a significant influence on the accountability performance of government agencies.